Effectiveness of the Rumoh Gizi Gampong (RGG) program to increase coverage of specific and sensitive indicators for accelerating stunting reduction in Aceh - Aripin Ahmad; Eva Fitrianingsih; Silvia Wagustina (AcTion: Aceh Nutrition Journal, 2023)
Aceh is the province with the fifth-highest prevalence of stunting in Indonesia by 2022, which could be due to the low coverage of specific and sensitive intervention programs. This research aims to determine the effectiveness of the Rumoh Gizi Gampong (RGG) program in increasing the coverage of specific and sensitive indicators for reducing stunting in Aceh. A cross-sectional design was carried out in Aceh Province from February to September 2023. The input, process, and output variables for RGG implementation were collected using interview methods with 21 RGG program managers and 23 people in charge of district nutrition programs. Specific and sensitive indicator achievements were collected using secondary data from district reports for the years 2020 and 2021. Data analysis was performed using a Dependent T-test at a confidence level of 95%. The results showed that there was an increase in the average percentage coverage of specific and sensitive indicators after the RGG program was implemented, and only the immunization coverage indicator was implemented using the yard. The results of the statistical analysis showed a significant increase in the percentage of coverage of the health insurance service coverage indicator (p= 0,006). In conclusion, the Rumoh Gizi Gampong program can increase the coverage of indicators to accelerate stunting reduction, so that villages can make RGG an alternative intervention to accelerate stunting reduction.